1992
DOI: 10.1115/1.2905473
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Measuring Adhesion Strength of IC Molding Compounds

Abstract: Adhesion strength evaluation of molding compounds is a critical issue in structural design and material selection for IC plastic packages. However, since conventional adhesion tests can only give apparent adhesion strengths, which include the effect of residual stress, their results cannot be used for design purposes. This paper proposes a new strength evaluation method which can experimentally separate residual stress from adhesion strength. In this method, three-point bending tests of ENF specimens are perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…[32]. Nishimura et al [50] reported that the values of the stress intensity factor for different interfaces in the case of mode II fracture were 1.2 MPa・m 1/2 . These values were obtained upon conducting the bending test from the resin section of the test piece, to which the IC sealing resin and the lead frame material (Fe-42Ni) were bonded.…”
Section: Identification Of the Location Of The Crack Tipmentioning
confidence: 99%
“…[32]. Nishimura et al [50] reported that the values of the stress intensity factor for different interfaces in the case of mode II fracture were 1.2 MPa・m 1/2 . These values were obtained upon conducting the bending test from the resin section of the test piece, to which the IC sealing resin and the lead frame material (Fe-42Ni) were bonded.…”
Section: Identification Of the Location Of The Crack Tipmentioning
confidence: 99%
“…Two cylindrical steel rods were then tested using the Instron Micro Tester-Universal Testing machine manufactured by Instron in Norwood, MA, USA with a constant rate of 1 mm/min continually drawn apart in tensile mode until the coating samples on the cylindrical steel rods tore apart. The adhesion strength of the coating sample in MPa is calculated based on the following Equation (1) [21]: (1) where, adhesion strength MPa ; maximum load at rupture N ; adhered area mm .…”
Section: Scanning Electron Microscopy (Sem) Analysismentioning
confidence: 99%
“…Hauck et al [10] determined the interface fracture property with mixed mode phase angle from 0° to 90° by employing CTS (Compact Tension Shear) specimen. Nishimura et al [11] determined the interface fracture property with ENF (End-Notch Flexure) specimen to exclude the impact of residual stress of thermal expansion, hygro-swelling and curing shrinkage. The mixed mode phase angle of ENF is about 80° [12].…”
Section: Numerical Analysis Of Interface Cracking In Plastic Packagingmentioning
confidence: 99%